Distributed Ledger Technology Experiments in Payments and Settlements - Shabsigh, Ghiath; Khiaonarong, Tanai; Leinonen, Harry (Washington, D.C. : International Monetary Fund, 2020)
Major transformations in payment and settlements have occurred in generations. The first generation was paper-based. Delivery times for payment instruments took several days domestically and weeks internationally. The second generation involved computerization with batch processing. Links between payment systems were made through manual or file-based interfaces. The change-over period between technologies was long and still some paper-based instruments like checks and cash remain in use. The third generation, which has been emerging, involves electronic and mobile payment schemes that enable integrated, immediate, and end-to-end payment and settlement transfers. For example, real-time gross settlement systems have been available in almost all countries. DLT has been viewed as a potential platform for the next generation of payment systems, enhancing the integration and the reconciliation of settlement accounts and their ledgers. So far, experiments with DLT experimentations point to the potential for financial infrastructures to move towards real-time settlement, flatter structures, continuous operations, and global reach. Testing in large-value payments and securities settlement systems have partly demonstrated the technical feasibility of DLT for this new environment. The projects examined analyzed issues associated with operational capacity, resiliency, liquidity savings, settlement finality, and privacy. DLT-based solutions can also facilitate delivery versus payment of securities, payment versus payment of foreign exchange transactions, and efficient cross-border payments.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet